Mechanics Of Fluids - Potter, Merle C., editor 271639 (Stamford, Conn : Cengage Learning, 2012)
Presents fluid mechanics in a manner that helps students gain both an understanding of, and an ability to analyze the important phenomena encountered by practicing engineers. The authors succeed in this through the use of several pedagogical tools that help students visualize the many difficult-to-understand phenomena of fluid mechanics.